Trends in Data Protection and Encryption Technologies - Mulder, Valentin; Mermoud, Alain; Lenders, Vincent; Tellenbach, Bernhard (Springer Nature, 2023)
This open access book reports the results of a study conducted in Switzerland in 2022 to provide an overview of the changing landscape of encryption and data protection technologies and their global usage trends. The Swiss Confederation tasked the Cyber-Defence Campus (CYD Campus) to identify the 38 most relevant encryption and data protection technologies, analyze their expected evolution until 2025, and derive implications for the military, civil society, and economy sectors. Fifty experts from academia, government, and industry have contributed to this study and provided their viewpoints on the different technologies and trends. This comprehensive collection of factsheets provides a reference for organizations and individuals that need to elaborate coherent and efficient data protection and encryption strategies in the coming years. The 38 technologies have been sorted into five categories. First, encryption foundations represent the technologies used to create other encryption applications. Second, low-level applications represent the technologies that focus on micro functionalities. Third, high-level applications represent the technologies that focus on more abstract and macro functionalities. Fourth, data protection represents the technologies used to protect data without encrypting these data. Finally, use cases represent concrete ways the different technologies can be used together to create a working solution. The book serves as a guide for decision-making within administrations, government organizations, and industry. It will also be interesting for the tech-savvy board member or engineers looking to get an entry point into data protection topics. Last not least, the book will also be a valuable reading for anyone interested in data protection and encryption.